2015
DOI: 10.3390/ijfs3040431
|View full text |Cite
|
Sign up to set email alerts
|

Positive Alpha and Negative Beta (A Strategy for Counteracting Systematic Risk)

Abstract: Undiversifiable (or systematic risk) has long been an enemy of investors. Many countercyclical strategies have been developed to counter this. However, like all insurance types, these strategies are generally costly to implement, and over time can significantly reduce portfolio returns in long and extended bull markets. In this paper, we discuss an alternative technique, founded on the premise of physiological bias and risk-aversion. We take a behavioral discussion in order to contextualize the insurance like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Further, it is to be noted that the performance is also highly dependent asymmetric relationship magnitude of the markets and time horizon. Our results showed that all of the three strategies performed well and reacted in ways very much in line with the original study (Noddeboe & Faergemann, 2015 ).…”
Section: Robustness Check and Empirical Resultssupporting
confidence: 91%
“…Further, it is to be noted that the performance is also highly dependent asymmetric relationship magnitude of the markets and time horizon. Our results showed that all of the three strategies performed well and reacted in ways very much in line with the original study (Noddeboe & Faergemann, 2015 ).…”
Section: Robustness Check and Empirical Resultssupporting
confidence: 91%